PREDICTORS OF ACADEMIC PERFORMANCE - Blanca GRAMA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2016)
Developing capacities and skills necessary for the integration into the labour market and for the achievement of a professional career is a foreground target of the educational system. Within this frame, personality traits and career interests of students who shall pursue a career in education are directly connected to the choices they make, to their plans and achievements equally. This study presents an analysis of the dominant personality traits of the students studying physical education, based on the Big-Five model, based on the results of a quantity-quality descriptive study conducted on 118 students attending the physical and athletic education faculty, as well as the identification of the occupational cluster corresponding to the teaching activity. For the studying of the personality factors we used the NEOPI-R personality inventory, career interests were measured with the JVIS, Jackson Vocational Interest Survey, and the results were correlated with academic performance. As a result of the analysis, we may conclude that the physical education student is both an agreeable and a hard-working person, with a high sense of responsibility, constantly preoccupied for his personal performance.